GABA, Selank, and Olanzapine Affect the Expression of Genes Involved in GABAergic Neurotransmission in IMR-32 Cells - Filatova, Elena; Kasian, Anastasiya; Kolomin, Timur; Rybalkina, Ekaterina; Alieva, Anelya; Andreeva, Lyudmila; Limborska, Svetlana; Myasoedov, Nikolay; Pavlova, Galina; Slominsky, Petr; Shadrina, Maria (Frontiers in Pharmacology, 2017)
Clinical studies have shown that Selank had an anxiolytic effect comparable to that of classical benzodiazepine drugs, which can enhance the inhibitory effect of GABA by allosteric modulation of GABAA receptors. These data suggest that the molecular mechanism of the effect of Selank may also be related to its ability to affect the performance of the GABAergic system. To test this hypothesis we studied the changes in expression of 84 genes involved in the functioning of the GABAergic system and in the processes of neurotransmission in the culture of neuroblastoma IMR 32 cells using qPCR metod. As test substances, in addition to Selank, we selected the major GABAA receptor ligand, GABA, the atypical antipsychotic, olanzapine, and combinations of these compounds (Selank and GABA; Selank and olanzapine). We found no changes in the mRNA levels of the genes studied under the effect of Selank. The combined effect of GABA and Selank led to nearly complete suppression of changes in expression of genes in which mRNA levels changed under the effect of GABA. When Selank was used in conjunction with olanzapine, the expression alterations of more genes were observed compared with olanzapine alone. The data obtained indicate that Selank has no direct effect on the mRNA levels of the GABAergic system genes in neuroblastoma IMR-32 cells. At the same time, our results partially confirm the hypothesis that the peptide may affect the interaction of GABA with GABAA receptors. Our data also suggest that Selank may enhance the effect of olanzapine on the expression of the genes studied.